2020
DOI: 10.3389/fonc.2020.00616
|View full text |Cite
|
Sign up to set email alerts
|

A Nomogram for Predicting Distant Metastasis Using Nodal-Related Features Among Patients With Nasopharyngeal Carcinoma

Abstract: Distant metastasis is among the main reasons for treatment failure in nasopharyngeal carcinoma (NPC) patients. To identify patients with a high risk of distant metastasis is important to guide posttreatment surveillance, appropriate time treatments, and prolonging their long-term survival. In this study, we systematically examined the associations between a series of nodal-related characteristics and distant metastasis-free survival (DMFS) by detailed MRI reading and established a nomogram for DMFS in NPC pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 27 publications
2
26
1
Order By: Relevance
“…Numerous studies have shown that T stage is closely associated with locoregional recurrence, whereas N stage is associated with distant metastasis in NPC. 4,[22][23][24] A higher N stage is a risk factor for distant metastasis in NPC, 23,25 which is consistent with the results of our study.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Numerous studies have shown that T stage is closely associated with locoregional recurrence, whereas N stage is associated with distant metastasis in NPC. 4,[22][23][24] A higher N stage is a risk factor for distant metastasis in NPC, 23,25 which is consistent with the results of our study.…”
supporting
confidence: 90%
“…But MRI parameters are complex to acquire and are similarly not easy to apply clinically. 24 In our study, the nomogram constructed by combining CD4 + T lymphocytes, LDH, SF and N stage showed good predictive performance in both the training cohort (C-index = 0.763) and the validation cohort (C-index = 0.760). Moreover, circulating CD4 + T lymphocytes, serum LDH, and serum SF are readily detectable and inexpensive in the clinic with high reproducibility.…”
Section: Discussionsupporting
confidence: 55%
“…Recently a nomogram was proposed by Xie et al, using MRI‐related nodal features, including nodal necrosis and the number of involved nodes, to predict distant metastasis. Nodal size, nodal level, and ECE were not found to have a statistically significant correlation to outcome in this study 94 …”
Section: Nodal Features That Influence Prognosiscontrasting
confidence: 72%
“…Some studies suggested that these are not risk factors for distant metastasis. On the contrary, in the study by Xie et al [ 26 ], T stage, age-group, and EBV level were found to be independent risk factors for distant metastasis. In a propensity-matched analysis of 5929 Chinese patients with NPC, sex was found to significantly affect distant metastasis-free survival and females showed significant advantage over males in this respect [ 27 ].…”
Section: Discussionmentioning
confidence: 75%